(Un)Covering the COVID-19 Pandemic: Framing Analysis of the Crisis in Canada. Issue 2 (June 2020) - Poirier, William; Ouellet, Catherine; Rancourt, Marc-Antoine; Béchard, Justine; Dufresne, Yannick
Abstract : The current COVID-19 crisis is unprecedented in recent history. On April 1, 2020, the Secretary-General of the United Nations, Antonio Guterres, warned that the world was facing the most challenging crisis since World War II (Associated Press, 2020). With the pandemic taking on an unprecedented magnitude in the twenty-first century, it quickly monopolized media attention. As of early April, Radar+'s large dataset showed that about 65 per cent of headlines on major Canadian media websites were related to the COVID-19 pandemic.